Mastering Network Forensics : A practical approach to investigating and defending against network attacks - Jaswal, Nipun (BPB Publications, 2024)
Network forensics is a rapidly growing field with a high demand for skilled professionals. This book provides a comprehensive guide on the subject, covering everything from the fundamentals to advanced topics such as malware analysis and cyber attack investigation. Written by a seasoned expert with over 15 years of experience, this hands-on guide includes practical exercises in offensive security, Windows internals, reverse engineering, and cyber forensics. The book begins with the basics of network forensics, including concepts like digital evidence, network traffic analysis, and log analysis. It teaches you how to identify intrusion attempts, mitigate cyber incidents, and investigate complex cyber attacks. As you progress through the book, you will learn more advanced topics such as malware analysis, reverse engineering, and memory forensics. You will also learn how to use network forensics tools and techniques to investigate real-world incidents. This book concludes with a discussion of the career opportunities available in network forensics and teaches you how to find a job in the field and develop your skills.